A comparison between conventional radiography and digitized image accuracy in proximal caries detection - Pangnoosh M; Bashizadeh Fakhar H (Tehran University of Medical Sciences, 2003)
Statement of Problem: Computer Sciences, in radiology, like other fields, is of high importance. It should"nalso be noted that the accuracy of the technique and work conditions affects the radiographs information"nconsiderably. There for, in order to get more accurate diagnostic information, it seems necessary to investigate"ndifferent digitized radiographic techniques and to compare them with the conventional technique."nPurpose: The aim of this study was to compare the accuracy of conventional and digitized radiographic"nimages by three digitization techniques in proximal caries detection."nMaterial and Methods: In this research study, sixty extracted human canines, premolars and molars were"nmounted in blocks and imaged on E-Kodak film, similar to bitewing radiographs. Ten bitewing radiographs"nwere then scanned at 600 d.p.i with flat bed scanner and a digital camera, then digitized at 300 d.p.i with"nanother digital camera. The digitized images were displayed randomly on a high-resolution monitor. Six"nobservers assessed the caries status of 120 proximal surfaces by conventional and digitized images. The"nobserver's scores were compared with the results of the macroscopic examination. Reliability of each"ntechnique was calculated. Data were analyzed using chi-square and ANOVA tests."nResults: No significant differences were detected between different techniques in intact proximal surfaces and"nenamel caries diagnosis. However, digital techniques were more sensitive in dentin caries detection (P<0.05)."nConclusions: When conventional film images are digitized, medium resolution (300 d.p.i) seems to be"nsufficient. At this resolution the file size is decreased and there is no significant loss of the information"nnecessary for caries diagnosis.